Glabridin Attenuates the Retinal Degeneration Induced by Sodium Iodate In Vitro and In Vivo - Aung, Kaung Htet; Liu, Hua; Ke, Zongwen; Jiang, Shuang; Huang, Jianhua (Frontiers in Pharmacology, 2020)
Background Age-related macular degeneration (AMD) is one of the major causes of blindness in the elderly over the age of 60. AMD is divided into dry AMD and wet AMD. Although there are certain treatment methods for wet age-related macular degeneration (AMD), there are no effective treatments for dry AMD yet, and finding new drugs or treatment methods for dry AMD has become a priority. For this purpose, this study explored Glabridin (Glab), an isoflavane found in the root extract of licorice, which has never been investigated in relation to eye diseases. Purpose To investigate the effect of Glab on the sodium iodate (NaIO3) induced retinal degeneration in vitro and in vivo. Methods In vitro, cell viability and cytotoxicity were tested with methylthiazolyldiphenyl‐tetrazolium bromide (MTT) assay among the groups of ARPE-19 cells. The cell apoptosis was tested with Hoechst 33342 staining and flow cytometry. The level of Reactive oxygen species (ROS) was measured to check the effect on oxidative stress. The protein expressions of phosphorylation of ERK1/2 and p38 were detected by Western blotting. In vivo, C57BL/6J mice were pretreated with Glab intraperitoneally for one week and continued for 4 weeks. NaIO3 was given to mice through tail vein intravenous injection after 1 week of Glab administration. The retinas of mice were monitored by Optical coherence tomography (OCT) and electroretinography (ERG) at 1w, 2w, 3w, and 4w, respectively, followed by H&E staining. Results In vitro, the Glab protected the retinal pigment epithelial (RPE) cells against oxidative stress and apoptosis by inhibiting phosphorylation of ERK1/2 and the p38 MAPK pathway. In vivo, Glab significantly prevented retinal damage by stopping the progression of retinal degeneration and reducing the formation of deposits on the RPE layer induced by NaIO3. According to the findings of electroretinogram (ERG), Glab helped to maintain the normal function of the retina. Conclusion Glabridin has a protective effect against retinal degeneration. It is suggested that Glab be further investigated for the treatment of retinal degeneration diseases.